FIRST RECORD OF CERCOSPORA CITRULLINA LEAF SPOT ON LAGENARIA SICERARIA IN PAKISTAN - I. Mukhtar; S. Mushtaq; I. Khokhar; A.Hannan (Journal of Animal and Plant Sciences, 2013)
A leaf spot disease was observed on bottle ground [Lagenaria siceraria (Mol.) Standl.] from September to November 2011 in Lahore and Shiekhupura regions. Disease was characterized by irregular to obcircular, medium brown spots with distinct dark brown border on both sides of the leaves. Conidiophores were 2-30 in a divergent fascicle, simple, multiseptate, golden brown, however light paler to subhyaline at the apex, straight to slightly curved 3-5 × 50-300µm, geniculate and unbranched. Conidia were solitary, hyaline, filiform, 1-16 septate, non-constricted at the septa, 2.5-4×20– 270µm. The causal organism was isolated and identified as Cercospora citrullina on the basis of pathology and morphological characteristics. It is the first report of C. citrullina on L. siceraria from Lahore, Pakistan.
Keywords: Cercospora spot; Lagenaria; hyaline conidia; leaf spot